Favorable Outcome of Severe Acute Methadone Poisoning (Clinical Case) - G. A. Livanov (Obŝaâ Reanimatologiâ, 2018)
Purpose: to contribute to relief of metabolic disorders associated with hypoxia by including a succinate correcting tissue metabolism into the scheme of intensive care of acute severe methadone poisoning complicated by the crush syndrome.Materials and methods. We examined the dynamics of clinical manifestation of acute methadone poisoning complicated by crush syndrome: changes in clinical and biochemical parameters, coagulation test findings, blood gas composition and acid-base state, ECG and X-ray findings.Results. By the 7th day after patient's admission in the ICU, stabilization of hemodynamics, recovery of spontaneous breathing and consciousness, reduction of swelling and the beginning of the formation of pressure ulcers were observed; on the 8 the day, restoration of urination and characteristics of urine were registered. On the 12th day, the patient was transferred to the toxicology unit being in a state of moderate severity and demonstrating positive changes in all clinical parameters.Conclusion. The inclusion of a drug with antioxidant/antihypoxant properties in the infusion therapy scheme allows to relieve metabolic disorders associated with hypoxia, and thereby increase the effectiveness of treatment: i.e. to relief clinical and laboratory manifestations and reduce the ICU stay.